Objective Burma - Flynn, Errol; Walsh, Raoul; Wald, Jerry ([s.l.] : United Artists Corporation, 1972)
A thrilling, realistic account of the grim hardships facing men in battle as Errol Flynn leads a crack squadron of fifty American paratroopers behind enemy lines to destroy a Japanese radar base. But when an enemy ambush cuts off their escape route, they are forced into the savage swamp-infested hell of Burmese jungles
Errol Flynn, James Brown, William Prince, George Tobias
Copy available in DVD format
Keywords: World War, 1939 -- 1945 -- Campaigns -- Burma; World War, 1939 -- 1945 -- Motion pictures and war